ANALISIS KEBISISNGAN DAN DAMPAKNYA TERHADAP PRODUKTIVITAS KARYAWAN DI PLTM GUNUNG MERIAH KABUPATEN DELI SERDANG TAHUN 2024 - Prima, Armanda (Jurnal Penelitian Kesmasy, 2024)
Occupational safety and health (K3) aims to ensure that workers achieve optimal health, covering physical, mental, and social aspects. Occupational diseases are illnesses caused by work-related activities or the work environment. Workplace noise is a serious issue that can negatively impact workers' health. This study focuses on investigating “The Impact of Noise at PLTM Gunung Meriah in the Deli Serdang Region in 2024.” The research employs a quantitative approach. The total population in the study area consists of 72 employees, with a random sample of 42 respondents. Hearing impairment and reduced productivity were assessed using questionnaires and audiometry. Noise was directly measured with a sound meter, and data analysis showed noise levels ranging from 68.93 to 89.12 dB. The study found a significant correlation between noise levels and productivity, with a p-value of 0.005.